THE EFFECT OF RESERVOIR WATER LEVEL FLUCTUATION TO THE SEEPAGE ON EARTH DAM - H. Sudardja (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2012)
The modeling of earth dam was carried out in a drainage and seepage tank to analyze the seepage resulting from water level fluctuation in the upstream of the dam. The dam models were made of the mixture of Mt. Merapi sand deposit with the soil of sandy-silt from Wonosari area. The variations of sand content in the mixture were 100%; 90% and 80% and the upstream slope inclinations were 1:1; 1:1.5 and 1:2. The result showed that the dams with more sandy-silt in the mixture have smaller seepage and the dams with steeper upstream slope have greater seepage. During rapid rising of water level, the dams with steeper upstream slope have a high rising rate of upstream water level and higher height of downstream slope failure. Moreover, during rapid drawdown, the dams with gentler upstream slope have a smaller rate of upstream drawdown and lower height of upstream slope failure. The dams with more sandy-silt in the mixture have a higher value of rising rate and drawdown of upstream water level but lower height of downstream and upstream slope failure. In the dam management, continuous monitoring of the seepage resulting from reservoir water level fluctuation is required to avoid dam failure. Keywords: Earth dam, rapid rising, rapid drawdown, seepage, slope failure.